PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN KEMAMPUAN GERAK DASAR GULING DEPAN DALAM SENAM LANTAI - SYAMSUL HUDA, MUCHAMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In the conventional learning process, most of the material submitted by teachers were not completely understand by the students. This is  because there is no feedback between the material provided by the teacher and a student. It brings a bad result to the unmaximal student’s ability. Students will have under value of the KKM and percentage of students who no success more than 80%. It Seen from the initial assessment has been carried out on the material before forward rolling motion gymnastics floor, there are 12 students or 46.15% gain  criterion of